Narrative of the life of Frederick Douglass, an American slave, written by himself : With related documents - Douglass, Frederick (The Bedford series in history and culture, 2003)
This second edition of Douglass's Narrative reprints this classic document together with speeches and letters, all in a volume designed for undergraduate students. An extensive introduction places the Narrative in its historical and literary contexts with annotations on needed background.